2011
DOI: 10.1016/j.janxdis.2010.11.005
|View full text |Cite
|
Sign up to set email alerts
|

The moderational role of anxiety sensitivity in flight phobia

Abstract: Anxiety sensitivity (AS) is the tendency to interpret anxiety-related bodily sensations in a threatening way. Previous research in a subclinical population identified AS as a vulnerability factor in flight phobia: AS moderates the relationship between somatic sensations and flight anxiety. The present study aimed at gaining further evidence for the moderational role of AS in a large clinical population with flight phobia.The data were obtained from 103 participants: 54 flight phobic participants and 49 control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The findings of this study add to the growing number of studies investigating the role of important moderating variables (e.g., attentional control, anxiety sensitivity) in anxiety and phobia research [70, 71]. In addition, our study supports the finding that young adolescents in the general population have a relatively high likelihood of remission for social anxiety disorder and specific phobia.…”
Section: Discussionsupporting
confidence: 80%
“…The findings of this study add to the growing number of studies investigating the role of important moderating variables (e.g., attentional control, anxiety sensitivity) in anxiety and phobia research [70, 71]. In addition, our study supports the finding that young adolescents in the general population have a relatively high likelihood of remission for social anxiety disorder and specific phobia.…”
Section: Discussionsupporting
confidence: 80%
“…These two influences seem to be independent of each other. In addition, other factors may render an individual more vulnerable to developing a flying phobia, such as a genetic predisposition to anxiety, personal traits (e.g., anxiety sensitivity, [19,20] the tendency to interpret anxiety-related bodily sensations in a threatening way), or subclinical physiological dysfunctions. A critical evaluation of all the factors is given elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst some research has found that individuals with high anxiety sensitivity do not report a stronger increase in distress in response to phobic stimuli (e.g., flying-related videos) than those individuals with low anxiety sensitivity (Busscher et al, 2010 ), findings from a number of studies indicate a potentially important role for anxiety sensitivity in flying phobia. For example, research utilizing self-report questionnaires within the general (i.e., subclinical) population (Bogaerde and De Raedt, 2008 ) and within flying phobics (Bogaerde and De Raedt, 2011 ) has demonstrated that AS moderates the relationship between somatic sensations and flying anxiety, where somatic symptoms significantly predict flight anxiety in individuals with higher AS scores. Busscher et al ( 2013 ) examined the relationship between AS, flight anxiety and physiological arousal during in vivo exposure therapy.…”
Section: Anxiety Sensitivity and Other Pertinent Constructsmentioning
confidence: 99%